Comparison of zinc bioavailability in zinc-glycine and zinc-methionine chelates for broilers fed with a corn-soybean meal diet - Chen, Xiaohui; He, Chao; Zhang, Keying; Wang, Jianping; Ding, Xuemei; Zeng, Qiufeng; Peng, Huanwei; Bai, Jie; Lv, Li; Xuan, Yue; Bai, Shiping (Frontiers in Physiology, 2022)
The objective of this study was to compare the bioavailability of Zn from zinc-glycine (Zn-Gly) and zinc-methionine (Zn-Met) as compared with zinc sulfate (ZnSO4) used as a standard in broilers. A total of 1200 1-day-old male broilers (Cobb 500) were randomly allotted to 1 of 10 treatments with 8 replicate cages of 15 birds each. The broilers were fed a corn-soybean meal basal diet (containing 26.46 mg Zn/kg; control) or the basal diet added with 40, 80, and 120 mg Zn/kg as Zn-Gly, Zn-Met, or ZnSO4 for 14 days. The relative bioavailability (RBV) was calculated based on multiple linear regression slope ratios of Zn concentrations in tibia and pancreas, pancreas metallothionein (MT) concentration, and pancreas MT mRNA abundance on added Zn intake. When comparing the control with all Zn-supplemented treatments, Zn addition did not significantly affect average feed intake and bodyweight gain during day 1-14 (P > 0.10). However, Zn concentrations in tibia, pancreas, and liver, and pancreas MT concentration and MT mRNA abundance increased in all Zn-supplemented treatments compared with the control (P < 0.05), and these indices increased linearly (P < 0.001) with increasing added Zn level on day 7 and 14. The RBV of Zn as Zn-Met was similar to that as Zn-Gly or ZnSO4 (P > 0.40) on day 7 and 14, based on tibia and pancreas Zn. In contrast, on day 7 and 14, the RBVs of Zn were in the following order: Zn-Met > Zn-Gly > ZnSO4 (P < 0.05), based on pancreas MT concentration. The bioavailable Zn from Zn-Met was 1.20 or 1.25 times that from Zn-Gly on day 7 or 14, respectively, evaluated by pancreas MT content. The RBV of Zn as Zn-Met was similar to that as Zn-Gly or ZnSO4 on day 7, whereas it was higher than that as Zn-Gly or ZnSO4 on day 14, based on pancreas MT mRNA abundance. In conclusion, Zn-Met had higher bioavailable Zn than Zn-Gly for the starter broilers fed with the corn-soybean meal diet, using pancreas MT concentration as the response criterion.